1997
DOI: 10.1111/j.1600-079x.1997.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of melatonin and serotonin on glucose‐stimulated insulin release from perifused rat pancreatic islets in vitro

Abstract: Insulin plays a key role in the control of glucose homeostasis in mammals. Insulin secretion is regulated by a coordinated interplay of several factors. The role of the indoleamines in the control of insulin secretion has not been fully elucidated yet. The present study was addressed to investigate the function of melatonin and serotonin in the direct control of insulin secretion from the pancreatic islets. Explanted rat Langerhans' islets were treated with melatonin or serotonin while also being exposed to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 28 publications
(5 reference statements)
11
113
1
2
Order By: Relevance
“…It stimulates this process in the liver (Haagsmann et al, 1981;Cardonigra-Valino et al, 1997;Bremmer et al, 1999). The action of pineal gland hormone on insulin level had been observed earlier by Peschke et al (1997), who suggested a direct action of melatonin on the pancreatic islets (de Lima et al, 2001). Maćkowiak et al (1999a) and Fabiś et al (2002) also showed an increase in the levels of insulin in rats along with the simultaneous increase in the level of glucose after the administration of exogenous melatonin.…”
Section: Discussionmentioning
confidence: 76%
“…It stimulates this process in the liver (Haagsmann et al, 1981;Cardonigra-Valino et al, 1997;Bremmer et al, 1999). The action of pineal gland hormone on insulin level had been observed earlier by Peschke et al (1997), who suggested a direct action of melatonin on the pancreatic islets (de Lima et al, 2001). Maćkowiak et al (1999a) and Fabiś et al (2002) also showed an increase in the levels of insulin in rats along with the simultaneous increase in the level of glucose after the administration of exogenous melatonin.…”
Section: Discussionmentioning
confidence: 76%
“…The 2 h application of 10 nmol/l melatonin applied approximately at the maximum of the circadian oscillation (t = 22.9 h) caused a phase advance of around 9 h. After this the circadian period was maintained (t = 22.5 h); however, the amplitude was enhanced (from 92 to 155 pmol/l). To heighten the visualization of the phase shift, the hypothetic location of the curves (dotted lines) has been drawn before and after melatonin application effects of melatonin on insulin secretion from pancreatic rat islets in vitro reported previously [41,42]. Our results indicate that melatonin, as a hormonal Zeitgeber, influences the circadian rhythm of insulin release under in vitro conditions causing phase advances.…”
Section: Discussionmentioning
confidence: 88%
“…Perifusion of isolated rat pancreatic islets was performed as described earlier [42]. Briefly, about 300 isolated pancreatic islets were packed into a 6.6 mm glass column together with Sephadex G-10.…”
Section: Methodsmentioning
confidence: 99%
“…Melatonin as an inhibitor of insulin secretion in isolated islets and beta cells Melatonin attenuates glucose-and KCl-stimulated insulin secretion from perifused rat islets [59]. The inhibitory effect of melatonin on insulin release from rat islets was later confirmed [60].…”
Section: Melatonin and Insulin Secretionmentioning
confidence: 91%